Unusual and Late Recurrence in Ovarian Adult Granulosa Cell Tumour: A Case Report - Noor, Serajun; Ahmed, Jashim Uddin; Chowdhury, Shahanara; Rahman, Zillur (Journal of Chittagong Medical College Teachers’ Association, 2013)
Granulosa cell tumour of ovary are rare hormonally active neoplasm characterized by indolent course, local spread with a preponderance for extremely late recurrence and high survival rate. We report a 60 year old lady presented in 2009 with aggressive looking growth in vulva 16 years after her total abdominal hysterectomy with Bilateral salphingo-ophorectomy with infracolic omentectomy for suspected stage granulosa cell tumour of ovary , confirmed by histopathology. She remained disease free for 13 years and in 2005 underwent resection of retroperitoneal mass with multiple peritoneal implant, confirmed to be a granulosa cell tumour after biopsy. Despite six course adjuvent combination therapy with complete response she presented after 4 years in 2009 with a second recurrence in vulva. She had tumour reductive surgery followed by chemotherapy and hormonal therapy but the disease was progressive. In conclusion late recurrence and repeat recurrence is a hallmark for granulosa cell tumour of ovary, so we emphasis the need for long term follow up and consider the possibility of recurrence when presented with acute abdomen after initial surgery for granulose cell tumour. But there is no standard management protocol and we review this patients treatment in the context of current literature. JCMCTA 2012 ; 23 (2): 42-46